Effect of plasma current in Plasma-MIG welding process to microstructure formation at heat affected zone of as welded carbon steel - Sidek, Nur Azmina (2020)
Plasma-Metal Inert Gas welding is a hybrid welding process that combines two welding method which is Plasma Arc welding and Metal Inert Gas welding. In this study, carbon steel was welded using plasma-MIG process with a different plasma current. The difference in plasma current results in the changes in the microstructure formation, mechanical and physical properties of steel especially at coarse grain heat affected zone (CGHAZ). The aims of this study are to investigate the effect of plasma current to the microstructure formation and mechanical properties of as welded carbon steel at CGHAZ. In this study, carbon steel has undergone Plasma-MIG welding process using five designated plasma current which are 0 A plasma current (conventional MIG), 25 A plasma current, 50 A plasma current, 75 A plasma current, and 100 A plasma current. The effect of plasma current on HAZ microstructure was observed using optical microscopy and electron backscatter diffraction (EBSD). The mechanical properties of as welded carbon steel have been identified by using microVickers hardness tester. The results show that plasma current affect the microstructure and mechanical properties of as welded carbon steel. As the plasma current increase, the HAZ area becomes larger and coarser. The steel hardness also increases with the increasing of plasma current. But, when compared to conventional MIG welding with 0 A plasma current, the microstructure and grain size in conventional MIG welding is larger and coarser than in plasma-MIG welding. The hardness value also increases in conventional MIG than the one in plasma-MIG welding. Overall, it can be said that the use of plasma-MIG welding is able to refine the grain size, increase the microhardness of as welded carbon steel and decrease the heat input through the reduction of cooling rate.